2010
DOI: 10.1017/s1755773909990300
|View full text |Cite
|
Sign up to set email alerts
|

Contesting Europe: the constitutive impact of discursive dynamics on national referendum campaigns

Abstract: A comparison of two referendum campaigns on Europe in France and Ireland shows two different patterns of mobilisation. Focusing on the perceived influence of the European treaties on national legislation on abortion, two different types of Euro-scepticism can be discerned. One is settled in a potentially universal project of ‘enlightenment’ (fearing the ‘criminalisation’ of abortion due to EU (European Union) regulations), the other is concerned with the defence of the nation’s democratic sovereignty against t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…He did so in the context of a leadership contest within the socialist party, and not least with a view to who would be the left's main candidate for the 2007 presidential election (see Hainsworth, 2006, p. 101;Crespy, 2008;Grossmann and Woll, 2011). As Fabius, contributors to the debate sought to empower or (re-) constitute themselves as legitimate actors through their speech acts (Seidendorf, 2010), and/or tried to anchor certain issues or discourses more firmly in the discursive and political landscape. Especially the antiglobalisation group ATTAC, founded in 1998, had a golden moment in the limelight as a key contributor to the No campaign, relating the constitution to anti-globalisation sentiments and discourses, now catapulted to the very forefront of national debate.…”
Section: The Referendum Debate and Dramatis Personaementioning
confidence: 99%
“…He did so in the context of a leadership contest within the socialist party, and not least with a view to who would be the left's main candidate for the 2007 presidential election (see Hainsworth, 2006, p. 101;Crespy, 2008;Grossmann and Woll, 2011). As Fabius, contributors to the debate sought to empower or (re-) constitute themselves as legitimate actors through their speech acts (Seidendorf, 2010), and/or tried to anchor certain issues or discourses more firmly in the discursive and political landscape. Especially the antiglobalisation group ATTAC, founded in 1998, had a golden moment in the limelight as a key contributor to the No campaign, relating the constitution to anti-globalisation sentiments and discourses, now catapulted to the very forefront of national debate.…”
Section: The Referendum Debate and Dramatis Personaementioning
confidence: 99%
“…Empirically, most studies support the issue‐voting perspective (Garry et al ), that is, that ‘how voters understood the EU polity, in particular whether membership is beneficial to one's own country, was a crucial factor in all the referendums’ (Glencross and Trechsel , p. 755; for similar findings focusing on campaigns and discourse see de Vreese and Boomgaarden ; Seidendorf ). In addition, the strategic behaviour of governing and opposition parties (Crum ), party cues combined with issues (Marsh ), and emotional voting (Garry ) explain referendum outcomes.…”
Section: Voting In Referendumsmentioning
confidence: 99%
“…Empirically, most studies support the issue-voting perspective (Garry et al 2005), that is, that 'how voters understood the EU polity, in particular whether membership is beneficial to one's own country, was a crucial factor in all the referendums' (Glencross and Trechsel 2011, p. 755; for similar findings focusing on campaigns and discourse see de Vreese and Boomgaarden 2005;Seidendorf 2010). In addition, the strategic behaviour of governing and opposition parties (Crum 2007), party cues combined with issues (Marsh 2015), and emotional voting (Garry 2014 We argue that research on direct democratic votes more generally can provide the EU literature with more 'traditional' approaches that help to better explain and empirically examine citizens' voting decisions in referendums, and thus referendum outcomes (Hug 2002).…”
Section: Voting In Referendumsmentioning
confidence: 99%
“…There is a need to compare cases in which discourses are effective, or have an impact on politics/policy, with cases where they fail, or matter to a lesser extent. In his study of the French and Irish referenda debates over the ECT, Seidendorf (2010) identified failed, or unsuccessful, discursive actions beside successful ones. This allows for a much better understanding of the dynamics and the relationship between discourse and power.…”
Section: Case Selectionmentioning
confidence: 99%